Modeling & simulation of micro reactor with nitration of 2-methyl-4,6 dihydroxy-pyrimidine - Mandal, Alok Kumar; Pandey, Raj Kishore; Asthana, Nandan; Kulkarni, Amol; Kulkarni, Bhaskar Dattatraya (Science and Technology of Energetic Materials, 2011)
Nitration of 2-methyl-4,6-dihydroxypyrimidine (MDP) using concentrated sulfuric acid and nitric acid as nitrating mixture is a highly exothermic and hazardous reaction. Conducting such reaction in a batch reactor follow an unsteady state and its trajectory depends on various important parameters such as initial reactor temperature, initial composition of reaction mass, temperature of circulating coolant, etc. However, over all productivity, process control and safety of the batch process is highly restricted due to lower surface to volume ratio. In the present work, an effort has been made to over come the limitations of batch reactor by using the novel micro reactor device. Micro reactor is having extremely high surface to volume ratio, which has been explored to carry out nitration of MDP both numerically as well as experimentally and the results were compared with conventional batch reactor. The micro reaction system has been modeled using two dimensional (2-D) heat flow and mass transfer equations. The kinetic rate equation for nitration of MDP has evaluated experimentally by differential method which is used in modeling of the micro reactor. The numerical results from the 2-D model for conversion and temperature profile along the length and radius of micro reactor have been compared with corresponding results obtained from batch reactor. In order to validate the model, several experiments were conducted in micro reactor set-up with the variation of flow rate, residence time, concentration, temperature, etc. The experimental results from micro reactor revealed that nitration of MDP takes place even at much lower concentration and lower residence time with better control of temperature profile. Also, the reaction takes place in laminar region compared to turbulent region in corresponding batch reactor setup.
Keywords: 2-D modeling; 2-methyl-4; 6 dihydroxypyrimidine; Batch reactor; micro reactor